2018
DOI: 10.1007/s00031-018-9481-x
|View full text |Cite
|
Sign up to set email alerts
|

Relating Tensor Structures on Representations of General Linear and Symmetric Groups

Abstract: For polynomial representations of GL n of a fixed degree, H. Krause defined a new "internal tensor product" using the language of strict polynomial functors. We show that over an arbitrary commutative base ring k, the Schur functor carries this internal tensor product to the usual Kronecker tensor product of symmetric group representations. This is true even at the level of derived categories. The new tensor product is a substantial enrichment of the Kronecker tensor product. E.g. in modular representation the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It follows that η is a natural isomorphism. For the converse, taking N = S, the commutativity of (18) shows that φ is an isomorphism.…”
Section: Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows that η is a natural isomorphism. For the converse, taking N = S, the commutativity of (18) shows that φ is an isomorphism.…”
Section: Modulesmentioning
confidence: 99%
“…In [17], Krause defined an internal tensor product (⊗) on the category of strict polynomial functors of a fixed degree d. Kulkarni, Srivastava, and Subrahmanyam [18], and independently, Acquilino and Reischuk [1] showed that this internal tensor product, via the Schur functor, is related to the Kronecker tensor product of representations of the symmetric group S d . Krause used this internal tensor product to introduce Koszul duality as the functor (∧…”
Section: Koszul Duality Of Strict Polynomial Functorsmentioning
confidence: 99%